The “New” Economics of Trade Agreements: From Trade Liberalization to Regulatory Convergence? - Grossman, Gene M.; McCalman, Phillip; Staiger, Robert W. (Econometrica, 2021)
What incentives do governments have to negotiate trade agreements that constrain their domestic regulatory policies? We study a model in which firms design products to appeal to local consumer tastes, but their fixed costs increase with the difference between versions of their product destined for different markets. In this setting, firms' profit‐maximizing choices of product attributes are globally optimal in the absence of consumption externalities, but national governments have unilateral incentives to invoke regulatory protectionism to induce firm delocation. An efficient trade agreement requires commitments not to engage in such opportunistic behavior. A rule requiring mutual recognition of standards can be used to achieve efficiency, but one that requires only national treatment falls short. When product attributes confer local consumption externalities, an efficient trade agreement must coordinate the fine details of countries' regulatory policies.